(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This study analyzes how fashion is linked to the construction of social and cultural identity in the suburbs of São Paulo. In order to do so, a bibliographic review about society, consumption and fashion was carried out. This research served as a basis for our research object, the social institution “Periferia Inventando Moda”, which, with educational and social actions, plays an important role in the fashion behavior of the suburb’s youth. By analyzing the performance of this entity, it was possible to understand consumption more clearly, but also of fashion production in the sense of pride, belonging and resignification of a geographical space recognized by poverty and lack of opportunities.